Noise level assessment of Mobile Telecommunication Base Stations Proximate to Residential areas in Accra, Ghana - Nkansah, Francis Kwaku; Agbosu, Worlanyo Kwabena; Adanu, Kekeli; Boakye, Maxwell Kwame (Program Pascasarjana Universitas Sriwijaya, 2024)
The installation of base stations in Accra and other urban centers meant to expand mobile phone network coverage has met opposition from the public. This study was carried out to assess the noise levels of generators utilized at the mobile telecommunication base stations focusing on noise levels from mobile telecommunication base stations in residential zonings only at the night (2200-0600). The methodology for data collection involved a quantitative approach using simple compliance coefficient data analysis. The study results showed that noise levels from generator sets at base stations in residential areas were not always below the Environmental Protection Agency’s (EPA) threshold of 48dB within the hours of 2200 to 0600 at a distance of 50m from base stations. There is, therefore, noise pollution in this perimeter which has been classified as a residential area with negligible or infrequent transportation. In this regard, district assemblies ought to strictly implement a minimum setback distance of not less than 50m of telecommunication BSs from the closest residential structure.